Tobacco, alcohol and substance use prevalence among 10th grade students: İstanbul sample - Ögel, Kültegin; Taner, Sevil; Y. Eke, Ceyda (Journal of Dependence, 2006)
Objective: The aim of this research is to evaluate the prevalence of tobacco, alcohol and substance use among 10th grade students, and to compare the findings with previous research. Method: The research was conducted among 10th grade students in İstanbul. 43 schools were sampled by using the multistage cluster sampling method. In order to be able to compare the results of the research with a previous research that was carried out in 2001, a similar sampling method and questionnaire was used. Results: Lifetime prevalence of tobacco use was 37%, alcohol use was 51.2%. The same rates were 5.9% for inhalant use, 5.8% for marijuana use, 4.4% for flunitrazepam use, 3.7% for benzodiazepine use, 3.1% for ecstasy use and 1.6% foe heroin use. When the risk for using tobacco, alcohol and substance at least once in lifetime is compared according to gender, it was found that males have greater risk for using any of these substances except for benzodiazepine. Tobacco and alcohol use was more prevalent among children of low income families while flunitrazepam was less prevalent compared to children of high-income families. Prevalence of tobacco use was higher among students enrolled in a private school while alcohol and heroin use was more prevalent among students enrolled in other type of schools. The least available substance was heroin. Nearly half of the students who had used one of these substances had obtained their first drug from an elder family member. Conclusion: It was observed that the lifetime prevalence of substances other than tobacco, alcohol and benzodiazepine had increased among 10th grade students in İstanbul. Unlike previous research findings the prevalence of substance use was similar in all socioeconomic status. It is thought that the attitudes and thoughts of the family regarding substance use is a risk factor.